2016
DOI: 10.21809/rilemtechlett.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oxychloride formation in pastes containing supplementary cementitious materials: Thoughts on the role of cement and supplementary cementitious materials reactivity

Abstract: Over the last decade many concrete pavements in North America have begun to show excessive damage at the joints. This damage appears to be due to two primary causes: classic freeze-thaw damage due to local saturation caused by the pooling of water at the joints, and formation of an expansive phase known as calcium oxychloride due to a reaction between chloride-based deicing salts and calcium hydroxide in concrete. This letter explores the formation of calcium oxychloride in cementitious matrices based on const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…binder composition (more than just the physical strength of the paste). Suraneni et al [40] studied the formation of calcium oxychloride in concrete. It is an expansive reaction that involves both calcium chloride, CaCl 2 , and calcium hydroxide, Ca(OH) 2 , as reactants.…”
Section: B Chemical Reaction With Deicing Saltmentioning
confidence: 99%
See 1 more Smart Citation
“…binder composition (more than just the physical strength of the paste). Suraneni et al [40] studied the formation of calcium oxychloride in concrete. It is an expansive reaction that involves both calcium chloride, CaCl 2 , and calcium hydroxide, Ca(OH) 2 , as reactants.…”
Section: B Chemical Reaction With Deicing Saltmentioning
confidence: 99%
“…As CaCl 2 is often used as de-icing chemical and as the calcium oxychloride formation is favored at low temperatures, the chemical attack aggravates the salt frost scaling. Suraneni et al [40] demonstrated that the use of fly ash limits calcium oxychloride formation, because the pozzolanic reaction consumes the calcium hydroxide formed during cement hydration, and then calcium hydroxide becomes in short supply for the calcium oxychloride formation. However, the degree of cement substitution needs to be high to effectively bring down the content of calcium hydroxide.…”
Section: B Chemical Reaction With Deicing Saltmentioning
confidence: 99%
“…Although not reported here due to space constraints, research has also been performed on other SCMs at different w:cm values (15,19). Thermogravimetric analysis was performed on ground, hydrated powder to determine the CH content.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Several strategies have been proposed to mitigate CAOXY formation (14)(15)(16)(17)(18)(19). First, the use of supplementary cementitious materials (SCMs) such as fly ash, slag, and silica fume lead to a reduction in CAOXY contents due to a reduction in CH contents (14,18,19). Second, topical sealers can be used to create a physical barrier between CH and salt solution to prevent their reaction (14).…”
Section: Reducing Joint Damage Caused By Salt-matrix Reactionsmentioning
confidence: 99%
“…The former mechanism can be resolved through utilizing air-entrained admixtures which can establish an adequate void system to resist ice expansion pressures [10,11]. The latter can be addressed through using proper supplementary cementitious materials (SCMs) as a partial replacement of ordinary portland cement (OPC) to improve the durability of concrete in the presence of deicing salts through dilution and/or pozzolanic reactions [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%